Observational Scales for Assessing Cognitive Development of Persons With Moderate (Kapp_sniu), Severe (Kapp_sniz) and Profound (Kapp_snig) Intellectual Disabilities - Characteristics of the Tool - Beata Papuda-Dolińska; Anna Błaszczak; Katarzyna Wiejak; Tomasz Knopik; Grażyna Krasowicz-Kupis; Magdalena Łuniewska-Etenkowska; Piotr Zieliński (Maria Curie-Skłodowska University, Lublin, Poland, 2023)
Introduction: On the basis of education, the criterion-referenced diagnosis of the disorder does not provide sufficient grounds for planning educational and therapeutic support. The functional characteristics supplementing the data from the nosological diagnosis show the possibilities and difficulties of a person in functioning in the everyday life context. Research Aim: The aim of the article is to present observational scales for assessing the cognitive functioning of people with moderate (KAPP_SNIU), severe (KAPP_SNIZ) and profound (KAPP_SNIG) intellectual disabilities aged 6 to 25, which are part of the KAPP diagnostic battery. Evidence-based Facts: Current diagnostic instruments for the functional assessment of people with moderate, severe and profound intellectual disabilities contain outdated or non-standardized tools. In Poland, there is a need to supplement this catalogue. Summary: The scales are intended for functional assessment performed by special educators, psychologists and specialists. Theoretical assumptions on which the construction of the scales is based and the stages of this process, which included: pilot studies, standardization studies and validation studies, are presented. The psychometric properties of the scales as well as the data confirming convergent and differential validity are also described. The last chapter presenting the fields for interpretation of the results (inter-individual, intra-individual comparisons and between the parallel perspectives of the parent and teacher in the 270-degree diagnosis model) gives specialists a picture of the possibility of using tools in everyday diagnostic and therapeutic work.